2011
DOI: 10.1590/s0102-695x2011005000051
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antinociceptive and anti-inflammatory activities of Porophyllum ruderale (Jacq.) Cass., Asteraceae, aqueous extract

Abstract: Abstract:The present work investigated the antinociceptive and antiinflammatory activities of the Porophyllum ruderale (Jacq.) Cass., Asteraceae, aqueous extract (PRAE). For this purpose, acetic acid writhing, paw licking induced by formalin, hot-plate and pleurisy tests were performed. The doses of 100, 200 and 400 mg/kg (p.o.) significantly inhibited the writhing 63.4, 89.6 and 94.8%, respectively, in comparison with control group. The lick of the paw 1 st phase was reduced at the dose of 400 mg/ kg (24.9%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Therefore, the test can be used to clarify the possible mechanism of antinociceptive effect of a proposed analgesic drug. 24 Centrally acting drugs such as opioids inhibit both phases equally but peripherally acting drugs such as aspirin, indomethacin and dexamethasone only inhibit the late phase. The early phase is short-lived and initiates immediately after injection, being characterized by C-fiber activation due to peripheral stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the test can be used to clarify the possible mechanism of antinociceptive effect of a proposed analgesic drug. 24 Centrally acting drugs such as opioids inhibit both phases equally but peripherally acting drugs such as aspirin, indomethacin and dexamethasone only inhibit the late phase. The early phase is short-lived and initiates immediately after injection, being characterized by C-fiber activation due to peripheral stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that some phytotherapeutic agents are effective in accelerating the healing of burns [ 24 , 25 ]. P. ruderale is used in the folk medicine for cicatrization and its anti-inflammatory properties and cicatrizing activity [ 26 ]. Similarly, many experimental studies have found beneficial results with the use of low-level laser irradiation on burn wound healing [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P. ruderalle is used in folk medicine in Brazil for leishmaniasis, closing wounds, general pain, and internal bruising [24]. Some pharmacological properties have also been described for this plant, such as antioxidant, antimicrobial, anti-nociceptive, anti-inflammatory and antispasmodic activity [23,[25][26][27][28][29][30]. Due to the diuretic, anti-inflammatory and antioxidant properties of papaloquelite, and the close relationship either these biological activities and the development of kidney disease, this plant could be an important source of compounds for the treatment of KAI.…”
Section: Introductionmentioning
confidence: 99%